Town-village spatial restructuring in developed regions of China from the perspective of resident travel: a case of Lin’an district, Hangzhou - Lin Tian; Yao Cheng (Humanities & Social Sciences Communications)
Abstract The organization of town-village space in developed regions of China is undergoing profound restructuring, resulting in fundamental changes in the daily travel patterns of rural residents. However, current studies often focus on the static space itself, neglecting the dynamic interactions and functional shifts driven by the “users” of space. This study fills the gap by analyzing residents’ inter-village commuting and non-commuting travel links using mobile phone signaling data, combined with field research and questionnaire surveys. The findings reveal that the town-village spatial structure exhibits a combination of hierarchical and network patterns. First, the traditional “central place” model remains dominant, with central town centers forming radial connections with surrounding villages. However, localized networked structures have emerged, characterized by horizontal links among villages. Second, both commuting and non-commuting travel links have extended spatially, forming self-organized clusters with strong internal connections that do not strictly follow administrative boundaries. The linkages between rural and urban areas have also strengthened, following a logarithmic distance decay trend. Finally, the study highlights that technological advancements, industrial upgrading and diversification, and policy interventions are the main drivers of spatial restructuring. The findings provide valuable insights for town-village spatial planning and policy-making, emphasizing the need to consider actual functional relationships and resident behavior. These insights are important for rural areas in China and beyond in the context of rural transition.